Assessing Outcomes After Adrenalectomy for Primary Aldosteronism – Early is Accurate: Retrospective Cohort Study. Issue 5 (27th November 2022) - Suurd, Diederik P.D.; Vorselaars, Wessel M.C.M.; Van Beek, Dirk-Jan; Borel Rinkes, Inne H.M.; Spiering, Wilko; Valk, Gerlof D.; Vriens, Menno R.
Abstract : Objective: We aimed to investigate the postoperative trend in blood pressure (BP)-related outcomes [BP and antihypertensive (AHT) drug use] during the year following adrenalectomy for primary aldosteronism (PA) to determine the optimal timing for outcome assessment and to determine the necessary follow-up length. Background: Since the course of BP-related outcomes after adrenalectomy is unknown, the optimal timing of outcome assessment and follow-up duration are not clear. Methods: In this retrospective single center cohort study, we used a prospectively collected database with all patients referred for difficult-to-control-hypertension-analysis. All patients diagnosed with PA who underwent adrenalectomy were included. AHT drug use [in defined daily dose (DDD)] and home blood pressure measurements (HBPMs) during the first postoperative year were collected. A mixed-effects model was developed to assess the stability of DDD and HBPM over time and adjust for potential confounders. Results: In total 1784 patients were assessed for difficult-to-control-hypertension of whom 41 were included. Both the DDD and HBPM showed the strongest decrease in the first postoperative month (mean 1.6DDD; mean 140/85 mm Hg) compared with preoperative values (4.5DDD; 153/92 mm Hg). Thereafter, both outcomes showed a stable course from 4 to 6 months (1.6DDD; 136/86 mm Hg) up to 12 months postoperatively (2.0DDD; 136/83 mm Hg). Conclusions: This study showed that AHT drug use and HBPM decreased substantially within the first month after adrenalectomy for PA and afterwards generally remained stable during the year following adrenalectomy. We propose that BP-related outcomes can be assessed reliably early after adrenalectomy and question the need for routine long-term follow-up in referral centers.